Oman’s economic diversification cum trade structure - Hamid, Zarinah; Mohd Amin, Ruzita (Ministry of Higher Education, Sultanate of Oman, 2017)
In line with Oman‘s National Programme for Enhancing Economic Diversification "Tanfeedh" which has received the Royal approval and has been endorsed by the Royal Decree 1/2016, this paper attempts to analyze the potential success of economic diversification of Oman by adopting measurements of trade concentration profile as used in Pitigala (2005). Tanfeedh's mandate is to implement the ninth five-year plan (2016-2020), which calls for oil's contribution to GDP to decrease to 26 per cent. The government has chosen five sectors with which it sees its best potential, namely: manufacturing, transport and logistics, tourism, fisheries and mining. This paper investigates whether or not Oman possesses the necessary trade structure by analyzing her dynamic exports between the years 1990 to 2015. In addition, the HerfindahlHirschman concentration index is also being employed to measure trade concentration for selected years for Oman and other GCC countries as a comparison. The advantage of using these measurements at the disaggregated level is that they allow for a more in-depth analysis at the product level that could be used to gauge the prospects for the success of economic diversification. The findings of this paper provide useful information for the formulation of strategies that would enhance Oman‘s economic diversification programme "Tanfeedh". It also serves additional information as to whether it needs to realign the existing policies in order to promote a more favorable environment and sustainable development in Oman.